First record of Florometra magellanica (Bell, 1882) (Echinodermata: Crinoidea) in Peru - Prieto Rios, Elba (2011)
Florometra magellanica (Bell, 1882) (Echinodermata: Crinoidea) is reported for the first time from Peru. The species was collected in the continental slope (360 – 814 m) off Piura Department, Northern Peru (3°38.67’S, 81° 2.73’W). Reference material has been deposited in the Colección Cientifica del Instituto del mar del Perú (IMARPE), Lima, Peru and in the Colección Nacional de Equinodermos, Universidad Nacional Autonoma de Mexico, Mexico City.